Morphology, intrafetal vascular pattern, and umbilical artery Doppler indices of acardiac twins - Tuangsit Wataganara (2020)
© 2020 John Wiley & Sons, Ltd. Background: Twin reversed arterial perfusion (TRAP) sequence consists of acardiac twin (A) paradoxically perfused by pump twin (P) through an umbilical artery (UA). We proposed characterization of acardiac twins with intrafetal vascular pattern (IVP), and assessed its correlation with morphology and UA Doppler indices. Methods: We prospectively evaluated 21 cases of TRAP sequence. Morphology (acardia vs hemicardia) and IVP (simple vs complex) of acardiac twins were characterized with ultrasound and color Doppler. Twins weight ratio (A/P Wt) and UA Doppler indices of acardiac and pump twins including (1) difference of systolic/diastolic ratio (UA ∆S/D), (2) difference of resistance index (UA ∆RI), and (3) ratio of pulsatility index (UA PI A/P) were calculated. Results: The median (min, max) gestational age at diagnosis was 18 (11, 27) weeks. Acardia (n = 14) were associated with simple IVP (n = 16) (P <.05). After exclusion of acardia with complex IVP (n = 1), the A/P Wt, UA ∆S/D, UA ∆RI, and UA PI A/P of acardia with simple IVP (n = 13), hemicardia with simple IVP (n = 3), and hemicardia with complex IVP (n = 4) were not significantly different (P >.05). Conclusions: Most of acardiac twins were acardia with simple IVP. Morphology and IVP of acardiac twins were not associated with UA Doppler indices.